Analysing the social and cultural underpinnings of pre-Islamic Arabic poetry - Ahmad H.Osman, Rahmah (s.n, 2012)
The classic collection of seven qasidah's (al-Mu'allaqat al-sab'al-tiwal) offers an arguably reliable sample of pre-Islamic work. The anthropological study of pastoral-nomadic societies in the Middle East provides a useful lens for interpreting the social content of these Jahili odes and its relevance to the culture that composed them. Applying this approach to the themes of feud and food sharing prominent in the Mu'allaqat suggest that common scholarly views on these two issues may reflect pre-Islamic Arabian society's perceptions of itself rather than a more methodical and precise understanding of that society. when cast in the light of well-documented societies, the singularly hyperbolic language of the Jahili literary world reveals its realistic underpinnings in their common pastoral-nomadic lifestyle. Moreover, placing the seven odes in a pastoral-nomadic setting helps reconcile the dissenting social message within the poems. This study suggests that scholars can utilize these anthropological methods to augment historical and comparative poetic approaches in describing Jahili society and determining poetry's place in it